Priming by Hexanoic Acid Induce Activation of Mevalonic and Linolenic Pathways and Promotes the Emission of Plant Volatiles - Llorens, Eugenio; Camañes, Gemma; Lapeña, Leonor; García-Agustín, Pilar (Frontiers in Plant Science, 2016)
Hexanoic acid is a short natural monocarboxylic acid present in some fruits and plants. Previous studies reported that soil drench application of this acid induces effective resistance in tomato plants against Botrytis cinerea and Pseudomonas syringae and in citrus against Alternaria alternata and Xanthomonas citri. In this work, we performed an in deep study of the metabolic changes produced in citrus by the application of hexanoic acid in response to the challenge pathogen Alternaria alternata, focusing on the response of the plant. Moreover, we used 13C labeled hexanoic to analyze its behavior inside the plants. Finally, we studied the volatile emission of the treated plants after the challenge inoculation. Drench application of 13C labeled hexanoic demonstrated that this molecule stays in the roots and is not mobilized to the leaves, suggesting long distance induction of resistance. Moreover, the study of the metabolic profile showed an alteration of more than two hundred molecules differentially induced by the application of the compound and the inoculation with the fungus. Bioinformatics analysis of data showed that most of these altered molecules could be related with the mevalonic and linolenic pathways suggesting the implication of these pathways in the induced resistance mediated by hexanoic acid. Finally, the application of this compound showed an enhancement of the emission of 17 volatile metabolites. Taken together, this study indicates that after the application of hexanoic acid this compound remains in the roots, provoking molecular changes that may trigger the defensive response in the rest of the plant mediated by changes in the mevalonic and linolenic pathways and enhancing the emission of volatile compounds, suggesting for the first time the implication of mevalonic pathway in response to hexanoic application.